2018
DOI: 10.1097/spv.0000000000000565
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Portable Ultrasound Bladder Scanner Measurements of Postvoid Residual Volume in Women With Pelvic Organ Prolapse

Abstract: The portable bladder scanner accurately measures PVR in patients with pelvic organ prolapse and could be considered as an alternative to catheterized assessment. However, stage III/IV prolapse is associated with increased bladder scanner error, which should be considered when determining appropriate candidates for bladder scanner PVR assessment.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Previous research has shown that ultrasound diagnosis of bladder residual urine volume facilitates the assessment of bladder function in patients with diabetic neurogenic bladder [ 4 ] and features merits such as simplicity and a high safety profile compared to methods such as direct catheterization [ 5 ]. However, the results are easily influenced by the proficiency of the examiner [ 6 ]. Bulbocavernosus is the superficial muscle tissue that ensures the excretion of excrement from the urethra.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that ultrasound diagnosis of bladder residual urine volume facilitates the assessment of bladder function in patients with diabetic neurogenic bladder [ 4 ] and features merits such as simplicity and a high safety profile compared to methods such as direct catheterization [ 5 ]. However, the results are easily influenced by the proficiency of the examiner [ 6 ]. Bulbocavernosus is the superficial muscle tissue that ensures the excretion of excrement from the urethra.…”
Section: Introductionmentioning
confidence: 99%
“…Since PVR is not a static measure, there may be variability in the measurement of PVR based on technique, since both bladder scanner and catheterization were used to quantify residual urine after surgery. Theisen et al recently reported the accuracy of ultrasound bladder scanner in women with stage II or greater prolapse and concluded that the bladder scanner accurately measures residual, and only underestimated maximum bladder capacity by a mean of 21 mL compared to catheterization. Given the exchangeability of these two techniques in real‐world practice, in our study to minimize the effect that the technique used to obtain PVR could play on our outcome, we treated longest follow‐up PVR as a categorical variable in our analysis, with a PVR greater than 200 mL used to define elevated PVR after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, the greater the uri-nary volume and residual urine volume, and the more advanced prolapse stage, the more errors in PVR urine volume measured by ultrasonography due to urethra kinking. In previous studies, when the PVR urine volume of advanced prolapse stage patients as measured by ultrasonography, is more than 100 mL, urethral catheterization should be used to measure PVR urine volume [17,18]. Advanced prolapse stage patients may experience discomfort with the same urethral catheterization method, even though ultrasonography, is a non-invasive method.…”
Section: Introductionmentioning
confidence: 99%
“…There is an ultrasonography method that can substitute urethral catheterization for PVR urine volume measurement, but research indicates that urethral catheterization is better for advanced prolapse stage patients because ultrasonography accuracy is poor. Notably, an approach for improving the accuracy of PVR urine volume with ultrasonography for POP patients is needed [18,19]. This study was planned because advanced prolapse stage patients can use ultrasonography without urethral catheterization, but there is no other way to increase accuracy.…”
Section: Introductionmentioning
confidence: 99%